Al-Haimanah al-Siyāsiyah wa al-Sulṭawiyah fī al-Syi’r al-Inqilāb al-‘Uṡmāny wa Suquṭ al-Sulṭān ‘Abd al-Hamīd li Ahmad Syauqy ‘alā Asās Naẓariyah al-Haimanah li Antonio Gramsci - Etsha Ari Kusuma Dianti; Abdul Basid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The background of the researcher taking this research topic is because he is interested in studying international conflicts that have occurred and as an additional reference in the world of literature. The purpose of this study is to reveal the forms of political hegemony and power that exist in Ahmad Syauqi's poetry, namely Al Inqilabi Al-Uthmani wa Suquuthi Sulthan Abdul Hamid based on Antonio Gramsci's perspective of hegemony theory and to find the counter-hegemony that existed during the reign of Sultan Abdul Hamid. II. The type of research method used is a qualitative and descriptive research method using a sociological approach. The primary data source used in this research is a poem from a collection of diwans entitled